The perceptions of neonatal nurses' towards extremely preterm infants - Gallagher, Katie (2010)
Technological advances in neonatal care have meant that the survival rates of preterm infants have dramatically increased. Improvements in mortality have not been reflected in improvements in morbidity, however, and the chances of extremely preterm infants surviving free from serious morbidity remain low.